USE OF INFOGRAPHIC MEDIA IN FORMING LEARNING INTEREST AND CREATIVITY OF MADRASAH STUDENTS - Muhammad hasbullah Ridwan; Risma Ulyatul Izza (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2025)
This study aims to describe the use of infographic learning media in  fostering creativity and learning interest among tenth-grade students at Madrasah. The background of this study is based on the lack of variation in  learning media in the classroom, which has an impact on the low level of students’  learning interest and creativity, particularly in Indonesian language learning.  Infographic media were chosen as an alternative learning medium because of their  advantages in presenting material visually, concisely, and attractively, which are  expected to increase students’ engagement in learning. This study employed a  descriptive qualitative approach with tenth-grade students of Madrasah  as the research subjects. Data were collected through observation, interviews, and  documentation. Data validity was ensured through technique triangulation and  source triangulation, while data analysis was conducted through data reduction,  data presentation, and conclusion drawing. The results indicate that the use of  infographic media has a positive impact on students’ learning interest and  creativity. Students became more enthusiastic, active, and focused during the  learning process. The visual, colorful, and systematic presentation of materials was  able to attract students’ attention and reduce learning boredom. In addition,  students’ creativity developed through activities of creating simple infographics  and engaging in active classroom discussions. Therefore, infographic learning  media can be concluded to be effective in fostering students’ learning interest and  creativity and can serve as an innovative alternative learning medium in Indonesian  language learning at the Madrasah  level.